Heavy metals in human bones from the Roman Imperial Period: Public health problem in the Roman Empire: Heavy metals - Güler, Hatice; Güçlü Ekinci, Hilal Kübra (Journal of Surgery and Medicine, 2023)
Background/Aim: Heavy metals are elements known for their toxic effects even at low concentrations, and human exposure to these elements spans history. This study aimed to investigate trace element levels in the bones of individuals from the Roman Imperial Period. The objectives were to determine the values of specific metals, including heavy metals, make a rough comparison with present-day values, and gain insights into the environmental conditions of that era. Methods: Due to the use of dry bone samples, ethical committee approval was not required for this research. The study analyzed element levels in human bones dated back to the Roman Imperial Period (218-244 AD), unearthed in 2018 during excavations in Turkey-Kayseri. Only bones that archaeologists verified to belong to the specified period were included, while those with uncertain origins were excluded. The samples were taken from os coxae of 15 individuals (eight males and seven females) to analyze Ca, P, Zn, Cu, Pb, and Hg levels. Instrumental techniques such as Wavelength Dispersive X-ray Fluorescence (WDXRF) (X-ray fluorescence) and ICP-MS (Inductive Coupling Plasma-Mass Spectrometer) were used to determine element concentrations. The Ca/P ratio was assessed for diagenesis evaluation, and statistical analysis was performed using Statistical Package for Social Sciences (SPSS) 22.0, with a significance threshold set at P-value <0.05. Results: The Ca/P ratio for the general population was calculated as 2.34 (0.10). The mean concentrations of heavy metals in the bones were as follows: Cu 18.27 (11.04) ppm, Pb 13.30 (5.66) ppm, Zn 27.22 (13.84) ppm, and Hg 2.45 (2.86) ppm. The corresponding P-values for Ca, P, Ca/P, Cu, Zn, Pb, and Hg were 0.109, 0.120, 0.104, 0.063, 0.113, 0.089, and 0.070. No statistically significant difference emerged when comparing elemental accumulations between males and females. Notably, copper and mercury levels were higher in Roman Imperial Period bones than contemporary ones, whereas zinc levels were lower, and lead concentrations aligned with reference values. Conclusion: The study results underscore the historical exposure of Roman Imperial Period individuals to heavy metals. These findings suggest that environmental health concerns related to heavy metal exposure date back millennia, emphasizing the long-standing nature of this issue.